Conceptual Model of a Digital Sales System for Rural MSMEs Based on System Requirements Analysis - Raykes Hinrich Tuerah (Danadyaksa: Post Modern Economy Journal, 2026)
Rural Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in strengthening local economies; however, many still face limitations in market access, digital literacy, and the use of integrated sales systems. In Desa Tombatu, Minahasa Tenggara Regency, MSMEs have begun utilizing digital platforms and marketplaces, yet their use remains fragmented and unsupported by structured sales information systems. This study aims to analyze system requirements and develop a conceptual model of a digital sales system tailored to the characteristics of rural MSMEs. The research adopts a descriptive qualitative approach using system requirements analysis, supported by literature review and field observations. The findings identify two main categories of system requirements: functional and non-functional. Functional requirements include product and price management, automated sales transaction recording, inventory management, customer data management, digital payment integration, delivery management, and simple sales reporting. Non-functional requirements emphasize ease of use, simple interface design, data security, mobile accessibility, and system reliability under limited internet connectivity. Based on these requirements, a conceptual digital sales system model is proposed, incorporating the principles of the Technology Acceptance Model (TAM), particularly perceived usefulness and perceived ease of use. The proposed model serves as a foundational framework for developing a user-oriented and sustainable digital sales system, with the potential to enhance efficiency, competitiveness, and economic resilience of rural MSMEs.